Presowing Treatments on Germination and Seedling Growth of Terminalia arjuna in Terai Zone of West Bengal - GOPAL SHUKLA; SUMAN MALLA; SUMIT CHAKRAVARTY (Seed Research, 2026)
An experiment consisting of two cutting intensity and nine different chemical treatments consisting of water and conc. H₂SO₄ were analyzed to study their effect on germination and growth of seedlings of Terminalia arjuna at Pundibari, West Bengal during May to October 2006. Significantly better germination was obtained when the seeds were heavily pinched or seed coat nearly removed and dipped in conc. H₂SO₄ for one minute, respectively. Significantly better initial seedling growth was also recorded with these treatments. Moreover interaction of these two treatments gave the highest germinability of 73.33 %.